THE TEACHER’S INFLUENCE IN CURRICULUM POLICY IMPLEMENTATION - NDLOVU, BY FRANCIS (IJRDO- Journal of Educational Research, 2017)
This paper looks at the role played by teachers in curriculum policy effectuation. Teachers /educators are the major pillars in the teaching and learning process. Without doubt the mostimportant person in the practice curriculum is the teacher. With their knowledge, experience andcompetencies teachers are central to any curriculum policy improvement effort, they areresponsible for introducing the curriculum in the classroom and outside education companiesspend countless hours developing curriculum it is the teacher who knew best what the curriculumshould look like. After, all they work directly with the students who are meant to benefit fromthe curriculum. The key to getting teachers committed to an innovation is to enhance theirknowledge of the new policy or programme. Therefore policymakers should no longer assumethat curriculum implementation is a process that directly translates into classroom reality.Teachers are the ones who ultimately decide the fate of any educational enterprise.Consequently, teachers’ attitudes, feelings and perceptions should not be devalued before thelaunching of any innovation.